Disaster Risk and the Prospect of Enhancing the Resilience of the African Community in Auckland. Issue 2 (19th March 2020) - Odiase, Osamuede; Wilkinson, Suzanne; Neef, Andreas
Abstract : Many urban communities have emerged in Auckland as a result of international migration. A significant concern for these communities is the relocation from an environment of known risks and familial support to an unfamiliar environment. The concern is essential because of the hazardous landscape of Auckland and the expected impact of climate change, which is anticipated to increase the vulnerability of at‐risk communities. This research investigates how the African community could enhance its resilience to the challenges that may be posed by a potential disaster. Interviews with participants from two African communities were the source of data collection. The interview data were analyzed using the general inductive method for qualitative data analysis. The research discusses emergent themes in line with prior research on community resilience. This research suggests an improvement in community risk awareness, compensation mechanism, capacity building, and community cohesion to improve resilience. The success of these findings depends on the extent to which government agencies address them in future planning for resilience.